Rancang Bangun Dashboard Penjualan pada PT. XYZ dengan Microsoft PowerBI - Monica Saputra; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
One of the most popular and most widely used technologies among people today is the internet. Starting from studying, shopping, working, doing business, communicating, everything can be accessed only by using the internet or in other words referred to as online activities. People are now trying to expand their business online, one of which is PT. XYZ. This company is a retail company that has an online and offline distribution system and sells power tools and household appliances. This company already has an application-based system. Therefore, the dashboard design for this company will be used to provide a summary of sales for three months from tokopedia, shoppe, lazada and tiktok shop to make it easier for company leaders to make decisions. The data collection method was carried out by interviewing and dashboard design using the prototyping method. This design will produce a dashboard using the Microsoft PowerBI Desktop application which can provide visual information about PT.XYZ's sales data.